Design And Implementation Of A Cyber Physical System Of A Automated Wheather Station And Agricultural Node In Smart Farming - Aswin Mikel Komang; Rizki Ardianto Priramadhi; Denny Darlis (Jurnal Nasional SAINS dan TEKNIK, 2024)
This research focuses on the development of a Cyber-Physical System (CPS) for Smart Farming by integrating an automated weather station with an agricultural node. The automated weather station collects crucial meteorological data, includingtemperature, humidity, rainfall, wind speed, and solar radiation, while the agricultural node monitors soil conditions, nutrient levels, and pest presence. Through seamless wireless communication and cloud-based analytics, the system providesreal-time insights to farmers, enabling informed decision-making regarding irrigation, fertilization, and pest control. Fieldtrials have demonstrated improved crop yield, resource optimization, and reduced environmental impact, showcasing thepotential of this CPS to revolutionize modern agriculture and contribute to sustainable and efficient farming practices. TheAgricultural Node, on the other hand, incorporates various sensors and actuators to monitor and control essential factorssuch as soil moisture, nutrient levels, and pest presence.